(untitled) - Blanton, Linda Lonon (Boston, MA, 2001)
This classic, step-by-step approach emphasizes the fundamentals of great composition writing. Students develop writing skills to prepare them to make the transition from use of simple prose to more linguistically sophisticated and complex discourse.
Keywords: English language,English language; Textbooks for foreign speakers.,Composition and exercises